Antioxidant contribution of seminal plasma and its effect on the quality of frozen equine semen - Restrepo B., Giovanni (2019)
The seminal plasma (SP) has enzymatic and non-enzymatic antioxidants with the function of protecting sperm from the harmful effects of oxidative stress. The aim of this study was to evaluate the antioxidant contribution of SP during the freezing of equine semen and its effect on post-thawing sperm quality. The semen of five horses was collected, the SP was separated and supplemented in proportions of 0% (Control), 10% (PS10) and 20% (PS20) to the sperm fraction in the freezing extender. The total antioxidant capacity (TAC) was evaluated by the oxygen radical trapping capacity (ORAC) and ferric reducing capacity (FRAP) methods, and the activity of SOD, GPx and catalase enzymes by spectrophotometry. Fifteen ejaculates were subjected to freezing and motility (MOT), vitality (EV), morphology (AM), functional membrane integrity (MI) and mitochondrial membrane potential (MMP) of the sperm were evaluated. Mixed models were adjusted, the means were compared by the Tukey test and a correlation analysis was performed. PS10 and PS20 generated an increase in the TAC measured by FRAP and the catalase activity of the diluted semen (p<0.05). PS20 increased the MOT of thawed semen compared to the Control (p<0.05). A post-thawing reduction of MMP was observed due to PS10 and PS20 (p<0.05), and positive correlations were found between MMP and SOD activity. It is concluded that SP increases the total and enzymatic antioxidant capacity of stallion semen and influences mitochondrial activity and post-thaw sperm motility.